PENINGKATAN PENGUASAN KONSEP MATEMATIKA PADA MATERI POKOK PELUANG MELALUI MODEL PEMBELAJARAN KOPERATIF TIPE THINK PAIR SHARE DI KELAS IX-2 SMP NEGERI 2 TIGAPANAH TAHUN PELAJARAN 2018/2019 - Puji Muliani (Universitas Negeri Medan, 2021)
Abstract: This study aims to determine the increase in mastery of concept mastery and student learning activities on the subject matter of opportunities by applying the think pair share type of cooperative learning model in class IX-2 of SMP Negeri 2 Tigapanah in the 2018/2019 school year. This classroom action research took place in two cycles. The research was conducted from January 2019 to April 2019. The research subjects were all students of class IX-2 SMP Negeri 2 Tigapanah for the 2018/2019 academic year, totaling 26 students. Students' concept mastery data was obtained through tests, while learning activity data was obtained through observation of learning activities. The results showed that; 1) students' mastery of concept mastery increases by applying think pair share cooperative learning model, as evidenced by student test results, learning mastery increases by 19%. In Cycle I the average test score was 72 with learning completeness of 69% and in Cycle II the average test score was 80 with learning completeness up to 88%, and succeeded in providing mastery of classical concept mastery; 2) student learning activities increase by applying the think pair share cooperative learning model, as evidenced by the observation that the percentage of active students increased by 19% with the percentage of active students in Cycle I of 73% and in Cycle II of 92%, and succeeded in providing complete learning activities. classic.Keywords: Concept Mastery, Think Pair ShareAbstrak: Penelitian ini bertujuan untuk mengetahui peningkatan ketuntasan penguasaan konsep dan aktivitas belajar siswa pada materi pokok peluang dengan menerapkan model pembelajaran kooperatif tipe think pair share di kelas IX-2 SMP Negeri 2 Tigapanah tahun pelajaran 2018/2019. Penelitian tindakan kelas ini berlangsung dalam dua siklus. Penelitian dilaksanakan pada bulan Januari 2019 sampai dengan bulan April 2019. Subjek penelitian adalah seluruh siswa kelas IX-2 SMP Negeri 2 Tigapanah tahun pelajaran 2018/2019 yang berjumlah 26 siswa. Data penguasaan konsep siswa diperoleh melalui tes, sedangankan data aktivitas belajar diperoleh melalui observasi aktivitas belajar. Hasil penelitian menunjukkan bahwa; 1) ketuntasan penguasaan konsep siswa meningkat dengan menerapkan model pembelajaran kooperatif tipe think pair share, terbukti dari hasil tes siswa ketuntasan pembelajaran naik sebesar 19%. Pada Siklus I rata-rata nilai tes 72 dengan ketuntasan pembelajaran sebesar 69% dan pada Siklus II rata-rata nilai tes 80 dengan ketuntasan pembelajaran naik menjadi 88%, dan berhasil memberikan ketuntasan penguasaan konsep secara klasikal; 2) aktivitas belajar siswa meningkat dengan menerapkan model pembelajaran kooperatif tipe think pair share, terbukti dari hasil observasi persentase siswa aktif naik 19% dengan persentase siswa aktif Siklus I sebesar 73% dan pada Siklus II sebesar 92%, dan berhasil memberikan ketuntasan aktivitas belajar secara klasikal.Kata Kunci : Penguasaan Konsep, Think Pair Share